Clozapine-specific proliferative response of peripheral blood-derived mononuclear cells in Japanese patients with clozapine-induced agranulocytosis. (September 2022) - Saito, Takeo; Usui, Toru; Inada, Hiroshi; Miyawaki, Izuru; Mizuno, Kentaro; Ikeda, Masashi; Iwata, Nakao
Background: Although clozapine-induced granulocytopenia (CIG) is less severe than clozapine-induced agranulocytosis (CIA), and some patients with CIG may not go on to develop serious complications, clozapine is discontinued in cases of both CIA and CIG. Understanding the pathogenic mechanisms of CIA/CIG could provide better management of clozapine therapy. Recently, as a mechanistic insight into adaptive immune systems, European groups reported clozapine-specific proliferative responses and clozapine-specific T cells using blood taken from patients with CIA and/or CIG. Aims: The aims of our study are to support this mechanistic evidence and to investigate the difference in the lymphocyte response to clozapine between patients with CIG and those with CIA. Methods: Lymphocyte stimulation tests (LSTs) were conducted using CD25-positive cell-depleted peripheral blood-derived mononuclear cells (PBMCs) isolated from blood of four Japanese patients with CIA, four patients with CIG, and nine clozapine-tolerant subjects. Results: Three of four patients with CIA and one of four patients with CIG showed proliferative responses to clozapine with a stimulation index of greater than 2. In contrast, none of the nine clozapine-tolerant subjects showed any response to clozapine. Olanzapine did not stimulate PBMCs of patients with CIA, patients with CIG, or clozapine-tolerant subjects. Conclusions: Clozapine- and CIA-specific lymphocyte reactions in a Japanese population provided supportive evidence that the pathogenesis of CIA is based on adaptive immune reactions. In addition, patients with CIG who show a positive response to an LST may at the very least not be chosen for clozapine-rechallenge and further prospective studies are desirable to verify this hypothesis.